2008
DOI: 10.1038/jcbfm.2008.143
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Inflammasome Complex Reduces the Inflammatory Response after Thromboembolic Stroke in Mice

Abstract: Inflammation is a major contributor to the pathogenesis of cerebral ischemia and stroke. In the peripheral immune response, caspase-1 activation involves the formation of a macromolecular complex termed the inflammasome. We determined whether nucleotide-binding, leucine-rich repeat, pyrin domain containing 1 (NLRP1), molecular platform consisting of capase-1, apoptosisassociated speck-like protein containing a caspase-activating recruitment domain (ASC), and NLRP1, is expressed in the normal and postischemic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
288
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 310 publications
(302 citation statements)
references
References 41 publications
14
288
0
Order By: Relevance
“…In the introduction we describe studies suggesting that NLRP3 inflammasomes contribute to ischemic brain injury (8,9), but that also NLRP1 inflammasomes are implicated in several models of brain injury (6,10,11), as are AIM2 inflammasomes (12). Here, using mice deficient in specific inflammasome components, we have shown that ischemic brain injury is profoundly influenced by multiple inflammasomes and, importantly, here was independent of the canonical sensor of sterile inflammation, the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the introduction we describe studies suggesting that NLRP3 inflammasomes contribute to ischemic brain injury (8,9), but that also NLRP1 inflammasomes are implicated in several models of brain injury (6,10,11), as are AIM2 inflammasomes (12). Here, using mice deficient in specific inflammasome components, we have shown that ischemic brain injury is profoundly influenced by multiple inflammasomes and, importantly, here was independent of the canonical sensor of sterile inflammation, the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the picture is more complicated. NLRP1 inflammasomes have been implicated in several models of brain injury (6,10,11), as have AIM2 inflammasomes, which are suggested to mediate pyroptotic neuronal cell death (12). There is also evidence supporting a role for caspase-1 in brain injury (13), with a selective caspase-1 inhibitor, VRT-018858, a nonpeptide, active metabolite of the prodrug pralnacasan, showing marked protection in a rat model of stroke (14).…”
mentioning
confidence: 99%
“…Most of the inflammasomes described to date contain an NLR protein, namely NLRP1, NLRP2, NLRP3, NLRP6, NLRP7, NLRP12, or NLRC4 (NLR-and caspase-activating recruitment domain-containing 4). 2,3 However, only few inflammasomes have been described and characterized in the CNS: The NLRP1 inflammasome in neurons, [4][5][6] the NLRP2 inflammasome in astrocytes, 7 the NLRP3 inflammasome in microglia, [8][9][10] and the absent in melanoma-2 (AIM2) inflammasome in neurons ( Figure 1). 11 However, other inflammasome sensors (including NLRP3, NLRP6, NLRP12, and interferon-g-inducible protein 16) may form inflammasomes in the CNS, but convincing data have not been generated to support this idea.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are several promising pharmacological candidates in use or in development that specifically target the inflammasome for the treatment of CNS inflammation after brain injury and stroke (de Rivero Vaccari et al, 2016a, b). Neutralizing antibodies targeting NLRP1 was reported to reduce CNS inflammation after stroke in mice (Abulafia et al, 2009). In addition, de Rivero Vaccari et al, 2008, 2016b reported that antibody neutralization of ASC reduced CNS inflammasome activation and inflammation after neural trauma.…”
Section: Future Directions Clinical Implications and Potential Thermentioning
confidence: 99%